2014
DOI: 10.6061/clinics/2014(04)02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutamine alone or in combination with zinc and vitamin A on growth, intestinal barrier function, stress and satiety-related hormones in Brazilian shantytown children

Abstract: OBJECTIVE:To determine the impact of supplemental zinc, vitamin A, and glutamine alone or in combination on growth, intestinal barrier function, stress and satiety-related hormones among Brazilian shantytown children with low median height-for-age z-scores.METHODS:A randomized, double-blind, placebo-controlled trial was conducted in children aged two months to nine years from the urban shanty compound community of Fortaleza, Brazil. Demographic and anthropometric information was assessed. The random treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…In the present study, we demonstrated in a mouse model that the RBD (regional basic diet, from Northeastern Brazil) promotes undernutrition during a short period of consumption (7 consecutive days), with the objective to understand the early intestinal pathophysiology of undernourished children in developing countries ( 24 , 25 ). In this model, moderate acute undernutrition is characterized by impaired growth, decreased crypt depth with no alterations in villus area, reduced basal I sc and disturbance of gene transcription in intestinal components of the nutrient transport systems in the ileum, with no accompanying changes in protein expression.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we demonstrated in a mouse model that the RBD (regional basic diet, from Northeastern Brazil) promotes undernutrition during a short period of consumption (7 consecutive days), with the objective to understand the early intestinal pathophysiology of undernourished children in developing countries ( 24 , 25 ). In this model, moderate acute undernutrition is characterized by impaired growth, decreased crypt depth with no alterations in villus area, reduced basal I sc and disturbance of gene transcription in intestinal components of the nutrient transport systems in the ileum, with no accompanying changes in protein expression.…”
Section: Discussionmentioning
confidence: 95%
“…Trp, as an essential amino acid in human nutrition, plays an important role in physical functions. Many studies have shown that dietary supplementation of L‐Trp could alleviate the stress response (Lima and others ). Our previous studies have shown that tryptophan supplementation reduced the catabolism of dietary amino acids and promoted protein synthesis in rats, promoted the oxidation of fatty acid, and reduced fat deposition in the body of rats (Jiang and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins are potent antioxidants: it was shown that dietary supplementation with vitamin E ameliorated hypoxia-induced intestinal damage in rats (Xu et al 2014). Also, in a double-blind trial conducted in Brazil, children prescribed with vitamin A, zinc and glutamine showed improved intestinal barrier function, possibly via interaction with leptin (Lima et al 2014). Dietary polysaccharides from wild jujube were shown to alleviate 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced intestinal barrier dysfunction in rats via modulation of TNF-α, IL-1β, IL-6 and myeloperoxidase (MPO) activities; and in the same study, the polysaccharides facilitated assembly of TJ proteins in Caco-2 cells stimulated with TNF-α (Yue et al 2015).…”
Section: Other Dietary Components and Food-derived Chemicalsmentioning
confidence: 99%